The Role Corn Varieties on Biomass, Stomata and Cholorophyll on a Nutrient Stress - Bukhari Bukhari; Nuryulsen Safridar (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
This study conducted on Soil and Plant of Laboratory, Screen House Experimental Farms on 2016 July until December on Agricultural Faculty, Syiah Kuala University, Darussalam Banda Aceh, Indonesia. This study used a Randomized Completely Design (RCD) with 36 treatments and three replications. They are have two factors such as Varieties have 9 procedures, and nutrient stress have 4 treatments. The parameter was observed on biomass, a total of stomata and chlorophyll. The result showed that varieties and nutrient stress were significantly on biomass, the whole of stomata and chlorophyll. The best of biomass was found on Sri Kandi kuning, and the lowest was found on anoman 1. The best of a total of stomata was found on anoman 1 and the lowest was found on sukmaraja. The heavy of chlorophyll was found on bima and the lowest was found on anoman 1. The best biomass was found on the nutrient of stress in formula AB and the lowest was found on magnesium. The best stomata on nutrient stress were found on formula AB, and the lowest was found on magnesium. The heavy of chlorophyll on stress hara was found formula AB and the lowest was found on Kalium. The best combination on biomass was found Sri Kandi Kuning and formula AB, the lowest was found on anoman 1 dan magnesium. The best combination on stomata was found on gumarang and formula AB, dan the lowest was found on sukmaraja dan magnesium.